Greening Schools, Greening Communities: Climate-Responsive CSR in Philippine Education - Hazel S. Osano; Anik Yuesti; Joel Arante Alve; I Komang Oka Permadi (International Journal of Applied Science and Sustainable Development (IJASSD), 2026)
Climate-related disruptions and environmental risks were shown to have direct effects on learning continuity, health, and school operations in the Philippines. This research synthesized recent literature and current policy guidance to explain how education providers reframed CSR from occasional clean-up drives into climate-responsive practices that were planned, measured, and sustained. The review indicated that credible “greening” work relied on three elements: risk- aware continuity planning, whole-school operational routines (water, sanitation, waste, energy use, and campus safety), and community partnerships that addressed local priorities. Results also suggested that programs became more durable when environmental actions were linked to quality assurance routines and learning activities rather than treated as seasonal campaigns. A practical policy direction emerged from the evidence: schools needed a right-sized sustainability agenda with clear ownership, simple indicators, and transparent reporting of progress and limits.